Relationship between adiponectin and blood pressure in obese Latino adolescent boys with a family history of type 2 diabetes - Kristin Hijazin; Brandon Smith; Coleby Garrett; Allan Knox; Louise A. Kelly (BMC, 2023)
Abstract introduction Adipokines are associated with several pathological states including, metabolic syndrome, obesity, insulin resistance and type 2 diabetes. One of these adipokines, adiponectin is of particular interest as it has been shown to have numerous anti-inflammatory effects, However, the association between adiponectin and blood pressure remains inconclusive especially in the Latino adolescent with obesity. Purpose To investigate the relationship between plasma adiponectin and blood pressure in Latino adolescents' boys with obesity and a with a family history of Type 2 diabetes. Methods Thirty two Latino adolescent males with obesity aged 14-17 years with a family history of type 2 diabetes underwent a frequently sampled glucose tolerance test (FSIVGTT) to measure insulin sensitivity. Body composition was assessed using dual energy x-ray absorptiometry. Obesity was defined as having a BMI percentile ≥95. Blood pressure was assessed using the Dinamap automated blood pressure monitor, and the average of three readings was used in the analysis. Fasting plasma adiponectin was determined using radioimmunoassay. Results There were moderate positive significant correlations for adiponectin and Systolic blood pressure(SBP) (rho = 0.436, p < 0.027) and Diastolic blood pressure(DBP) (rho = 0.41,p < 0.028). A multivariate liner regression showed that plasma adiponectin could significantly detect 19% of the variance in SBP (p = 0.017, and 33% for DBP (p = 0.017). In a simple linear regression adiponectin was not related to any of our variables (p < 0.05). Conclusion In conclusion, adiponectin was positively and significantly correlated to blood pressure in Latino adolescent with obesity. Future studies should investigate this relationship in a large sample of Latino adolescent youth.